2010
DOI: 10.1021/nl903760k
|View full text |Cite
|
Sign up to set email alerts
|

Surveying Molecular Vibrations during the Formation of Metal−Molecule Nanocontacts

Abstract: Molecular junctions have been characterized to determine the influence of the metal contact formation in the electron transport process through a single molecule. With inelastic electron tunneling spectroscopy and first-principles calculations, the vibration modes of a carbon monoxide molecule have been surveyed as a function of the distance from a copper electrode with unprecedented accuracy. We observe a continuous but nonlinear blue shift of the frustrated rotation mode in tunneling with decreasing distance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 32 publications
4
47
0
Order By: Relevance
“…8(a)], we find a large signal for the low-frequency FTs and the FRs with hardly any contribution from the stretch modes. The resulting IETS curve is a well-defined double-peak structure which is in line with previous experimental 13,14 and theoretical 14,34,35 studies for the same system. However, our FT contribution seems to be overestimated with respect to these works, where a similar height was found for the FT and FR modes.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…8(a)], we find a large signal for the low-frequency FTs and the FRs with hardly any contribution from the stretch modes. The resulting IETS curve is a well-defined double-peak structure which is in line with previous experimental 13,14 and theoretical 14,34,35 studies for the same system. However, our FT contribution seems to be overestimated with respect to these works, where a similar height was found for the FT and FR modes.…”
Section: Resultssupporting
confidence: 89%
“…14,44 These studies showed that the contribution of the inelastic processes tends to increase the total current in the former regime, which is in accordance with our LOIT approach where expression (43) has the same sign as its elastic counterpart (42). However, in those studies the AO basis employed was rather localized and therefore, as shown in Sec.…”
Section: B Iets Dependence On Tip-sample Distancesupporting
confidence: 82%
See 2 more Smart Citations
“…By studying these subtle changes of the vibrational energy using STM-IETS with a molecularfunctionalized tip, it has been demonstrated that STM-IETS can provide information on the inner structure of a molecule [4,5] similarly to atomic force microscopy (AFM) [6]. These advantages of STM-IETS have accelerated research in related fields [7][8][9][10][11][12][13][14][15][16]. Owing to recent progress in the theoretical description of IETS [17][18][19][20][21][22], the qualitative understanding has been improved considerably: the symmetry of the wave functions of a tip and a molecule on a substrate and a vibrational mode of the molecule are predicted to influence the efficiency of the inelastic process (γ inel ) for the tunneling current involving the molecule.…”
mentioning
confidence: 99%